A Novel Approach: Colon Targeted Drug Delivery System - Shweta S. Kulkarni; Jayashri S. Kolsure; Deepak A. Joshi (International Journal of Pharma and Bio Sciences, 2020)
A considerable attention from the past few years towards the drug delivery system approached a new drug delivery system, which is able to release drugs specifically in the colon in a predictable and reproducible way. This system is called “Colon specific drug delivery system”. The colon is the lower part of the GIT and large intestine where both local and systemic delivery of drugs takes place. To achieve successful colon targeted drug delivery, a drug needs to be protected from degradation, release and absorption in the upper portion of GIT and then ensure an abrupt or controlled release in proximal colon. Colonic drug delivery has gained increasing importance not just for delivery of drug for the treatment of local diseases associated with colon, like crohn’s disease, ulcerative colitis, inflammatory bowel disease, colon cancer, etc., but also for systemic delivery of proteins, therapeutic peptides, anti-asthmatic drug, anti-hypertensive drug and anti-diabetic agent. Colon is rich in aerobic and anaerobic micro flora thus, micro flora activated systems can be utilized efficiently to deliver drug molecules at the targeted site. Various approaches are formed based on prodrug formation, pH-sensitivity, time dependency (lag time), microbial degradation and osmotic pressure etc. to formulate different dosage forms like tablet, capsule, multiparticulate, microsphere and liposome for colon targeting, with the use of different polymers. CDDS can provide therapeutic benefits including better acceptance by patients, because these are pain- free, self-administer able as well as available at lower cost. In this review, recent advancement for designing CDDS, colon anatomy and physiology, colon related diseases, polymers used in CDDS dosage form and their pharmaceutical applications are reviewed with a particular emphasis on formulation technology.